The intriguing nature of the high-energy gamma ray source XSS J12270-4859 - De Martino, D. (2010)
The nature of the hard X-ray source XSS J12270-4859 is still unclear. It was claimed to be a possible magnetic Cataclysmic Variable of the Intermediate Polar type from its optical spectrum and a possible 860 s X-ray periodicity in RXTE data. However, recent observations do not support the latter variability, leaving this X-ray source still unclassified. To investigate its nature we present a broad-band X-ray and gamma ray study of this source based on a recent XMM-Newton observation and archival INTEGRAL and RXTE data. Using the Fermi/LAT 1-year point source catalogue, we tentatively associate XSS J12270-4859 with 1FGL J1227.9-4852, a source of high energy gamma rays with emission up to 10 GeV. We further complement the study with UV photometry from XMM-Newton and ground-based optical and near-IR photometry. We have analysed both timing and spectral properties in the gamma rays, X-rays, UV and optical/near-IR bands of XSS J12270-4859. The X-ray emission is highly variable showing flares and intensity dips. The flares consist of flare-dip pairs. Flares are detected in both X-rays and UV range whilst the subsequent dips are present only in the X-ray band. Further aperiodic dipping behaviour is observed during X-ray quiescence but not in the UV. The broad-band 0.2--100 keV X-ray/soft gamma ray spectrum is featureless and well described by a power law model with Gamma=1.7. The high energy spectrum from 100 MeV to 10 GeV is represented by a power law index of 2.45. The luminosity ratio between 0.1--100 GeV and 0.2--100 keV is ~ 0.8, indicating that the GeV emission is a significant component of the total energy output. Furthermore, the X-ray spectrum does not greatly change during flares, quiescence and the dips seen in quiescence. The X-ray spectrum however hardens during the post-flare dips, where a partial covering absorber is also required to fit the spectrum. Optical photometry acquired at different epochs reveals a period of 4.32 hr that could be ascribed to the binary orbital period. Near-IR, possibly ellipsoidal, variations are detected. Large amplitude variability on shorter (tens mins) timescales are found to be non-periodic. The observed variability at all wavelengths together with the spectral characteristics strongly favour a low-mass atypical low-luminosity X-ray binary and are against a magnetic Cataclysmic Variable nature. The association with a Fermi/LAT high energy gamma ray source further strengths this interpretation.